2005
DOI: 10.1002/jmor.10332
|View full text |Cite
|
Sign up to set email alerts
|

Unusual intestinal lamellae in the nematodeRhabditophanes sp. KR3021 (Nematoda: Alloinematidae)

Abstract: The free-living nematode Rhabditophanes sp. has recently been placed in a clade of animal parasites and may be a unique example of a reversal to a nonparasitic lifestyle. Detailed morphological analysis of the intestine reveals the unusual and unique structure of splitting microlamellae forming a meshwork with cavities along the entire intestinal tract. Secretion vesicles were observed along the whole tract and along the length of the lamellae. It is suggested that these lamellae are adaptations to a different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…The current study, in corroboration with Kessel et al (1961), Shepherd and Clark (1976) and Willems et al (2005), shows that the morphology of the intestinal microvilli within the phylum Nematoda is more diverse than initially thought. Most remarkable, deviations of the usual finger-like intestinal microvilli have arisen independently several times within the phylum, their occurrence always being in parasitic or in parasitism-related nematodes.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…The current study, in corroboration with Kessel et al (1961), Shepherd and Clark (1976) and Willems et al (2005), shows that the morphology of the intestinal microvilli within the phylum Nematoda is more diverse than initially thought. Most remarkable, deviations of the usual finger-like intestinal microvilli have arisen independently several times within the phylum, their occurrence always being in parasitic or in parasitism-related nematodes.…”
Section: Discussionsupporting
confidence: 91%
“…The type I vesicles observed in this study have been described frequently in nematodes as secretion vesicles (Bird & Bird, 1991;Borgonie et al, 1995;Willems et al, 2005) and are reported as having a double membrane (Borgonie et al, 1995). The thread-like type II vesicles that emanate from the top of the microvilli in the intestine of H. gingivalis have also been observed in Hexatylus viviparus (Shepherd & Clark, 1976), a nematode species that has a fungivorous as well as an entomoparasitic lifecycle.…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations